Marketing Innovation through the Identification of Business Model Canvas in Order to Enhance the Competitiveness of Micro, Small, and Medium Enterprises in Bondowoso Regency - Supriono Supriono; . Al-Musadieq; Topowijono Topowijono (e-2477-1929)
This study focused on the identification of marketing innovation model using the Business Model which was introduced by Alexander Osterwalder. The preparation of the marketing innovation model was based on the data and information obtained from interviews and secondary data (literature reviews) in the form of books, magazines, newspapers, the internet, and journals. The study was divided into 2 (two) stages: (1) identifying Marketing Characteristics of SMEs in Bondowoso; and (2) establishing a model of Marketing Innovation through Business Model Canvas. In this study, it was found that being passive in marketing and having limited access were the main problems faced by SMEs. Based on the data obtained, the marketing model offered was by classifying some of the elements involved in the marketing of SMEs to the Business Model Canvas having nine important factors. The first factor is Value Proposition by taking the government, distribution partners, investors, and suppliers as the elements. The second is Key Activities in the form of production, promotion, and distribution. The third is Key Resources in the form of human resources. The fourth is Value Proposition in the form of effective, efficient, and competitive marketing. The fifth is Customer Relationship in the form of bonus, discount, and total quality management. The sixth is Channel in the form of delivery service and the bureau of tourism. The seventh is Customer Segment in the form of customers from all economic, social, and cultural classes. The eighth is Revenue Stream in the form of profits from revenue. The ninth is Cost Structure in the form of cost incurred for the implementation process. Keywords: Innovation, SMEs, Marketing, Competitiveness, Business Model Canvas.